Patients’ Involvement in Decision-Making During Healthcare Visit in Karachi City, Pakistan: A Cross-Sectional Study - Ahmed, Syed Rizwan; Ahmad, Farah; Danish, Syed Hasan (Biological and Clinical Sciences Research Journal, 2025)
Shared decision-making (SDM) is a key component of patient-centred care that involves sharing information and reaching an agreement between healthcare practitioners and patients. Although globally acknowledged as a quality indicator in clinical treatment, SDM is still underused in many low- and middle-income countries (LMICs), including Pakistan. Objective: The purpose of this study was to evaluate patients’ involvement in SDM during outpatient consultations at a tertiary care hospital in Karachi, Pakistan. Methods: A cross-sectional study was conducted from 13-Nov-2024 to13-Jan-2025 involving a total of two hundred outpatients with long-term conditions, including diabetes, hypertension, heart disease, and gastrointestinal disorders. Derived from the SDM-Q9 instrument, data were collected through a semi-structured interview. When translated into Urdu, this questionnaire examined various aspects of SDM, including the degree of decision involvement, the time spent on consultation, and the level of sufficient information. Using SPSS version 27, data analysis comprised both descriptive and inferential methods. Results: The average age of participants was 51.9 years (±13.5), and the gender distribution was balanced. Despite 97.5% of participants indicating they were afforded time for reflection and 76% reporting empathetic communication, only 19.5% experienced sufficient shared decision-making. No significant associations were found between SDM scores and age, gender, education, marital status, or ethnicity (p > 0.05). Visual aids were underutilised, with only 28% of participants strongly supporting their use. Conclusion: Although contact between patients and doctors is improving, patients are still not involved in decision-making, indicating that they rely on doctor-led care. To improve shared decision-making in Pakistan, both cultural and structural barriers need to be addressed. This can be achieved by training providers, making decision aids available, and modifying the way institutions operate. Future studies should investigate treatments aimed at improving SDM in clinical settings.